2009
DOI: 10.1007/s00382-009-0650-4
|View full text |Cite
|
Sign up to set email alerts
|

Local and synoptic mechanisms causing Southern California’s Santa Ana winds

Abstract: The atmospheric conditions that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(146 citation statements)
references
References 25 publications
7
139
0
Order By: Relevance
“…We provide additional details of the physics parameterizations (e.g., boundary layer scheme, convection, ice microphysics, and cloud interactions) in the auxiliary material. Through comparison with point measurements, we have previously shown that the simulation reproduces local circulation statistics with a high degree of fidelity [Conil and Hall, 2006], including a specific validation of Santa Ana events [Hughes and Hall, 2010]. All major mountain complexes are represented in the weather simulation model (Figure 1), which is crucial for capturing wind corridors and meteorological patterns downwind of topography.…”
Section: Methodsmentioning
confidence: 91%
“…We provide additional details of the physics parameterizations (e.g., boundary layer scheme, convection, ice microphysics, and cloud interactions) in the auxiliary material. Through comparison with point measurements, we have previously shown that the simulation reproduces local circulation statistics with a high degree of fidelity [Conil and Hall, 2006], including a specific validation of Santa Ana events [Hughes and Hall, 2010]. All major mountain complexes are represented in the weather simulation model (Figure 1), which is crucial for capturing wind corridors and meteorological patterns downwind of topography.…”
Section: Methodsmentioning
confidence: 91%
“…Certain synoptic-scale conditions interacting with local topography contribute to Santa Ana occurrence (Yoshino 1975;Sommers 1978;Hughes and Hall 2010). This mid-February Santa Ana wind event commenced around 0000 UTC 15 February 2013, as maximum sea level pressures exceeded 1028 hPa in the Great Basin (Fig.…”
Section: The 14-16 February 2013 Event Observationsmentioning
confidence: 99%
“…Sommers 1978;Small 1995) that can produce gusts exceeding 45 m s 21 (100 mph) in favored areas. 1 The winds evince terrain-associated amplification of the mountain gap and downslope varieties (Huang et al 2009;Hughes and Hall 2010). Santa Ana events occur most frequently between October and February, with December being the peak month (Raphael 2003;Jones et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the massive destruction wrought by the Diablo winds, associated with the Northern California firestorm of October 2017 and the Oakland Hills firestorm of 1991, very little is known quantitatively about them, especially relative to the Southern California downslope winds that favor wildfires, such as Santa Ana [1][2][3][4][5][6][7][8][9][10] and Sundowner [11][12][13][14][15] winds. A prescient preliminary analysis of 'Santa Ana-like' winds in the Oakland Hills was performed in 1973 [16], some 18 years prior to the Oakland Hills fire of 1991, and analyses [17][18][19] subsequent to that fire confirmed their localization at the eastern San Francisco Bay Area.…”
Section: Introductionmentioning
confidence: 99%